2017
DOI: 10.1371/journal.pone.0180659
|View full text |Cite
|
Sign up to set email alerts
|

A novel isoform of IL-33 revealed by screening for transposable element promoted genes in human colorectal cancer

Abstract: Remnants of ancient transposable elements (TEs) are abundant in mammalian genomes. These sequences contain multiple regulatory motifs and hence are capable of influencing expression of host genes. TEs are known to be released from epigenetic repression and can become transcriptionally active in cancer. Such activation could also lead to lineage-inappropriate activation of oncogenes, as previously described in lymphomas. However, there are few reports of this mechanism occurring in non-blood cancers. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 108 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…1b). A comprehensive list of 702 oncogenes was generated from previously annotated onco-exaptation examples 4,15 and ONGene 19 (Supplementary Table 1). Considering the technical limitations of RNA-seq data, we set stringent filters (Methods) to maximize the specificity for onco-exaptation events.…”
mentioning
confidence: 99%
“…1b). A comprehensive list of 702 oncogenes was generated from previously annotated onco-exaptation examples 4,15 and ONGene 19 (Supplementary Table 1). Considering the technical limitations of RNA-seq data, we set stringent filters (Methods) to maximize the specificity for onco-exaptation events.…”
mentioning
confidence: 99%
“…In the present study, no mRNA or protein expression levels of IL-33 in HCT-116 cells were investigated due to it being demonstrated that IL-33 is undetectable in the HCT-116 colon cancer cell line ( 23 ). If IL-33 was determined to be highly expressed in this cancer cell line, then it may be necessary to knock out or block endogenous IL-33 to further confirm the initial data.…”
Section: Discussionmentioning
confidence: 99%
“…If IL-33 was determined to be highly expressed in this cancer cell line, then it may be necessary to knock out or block endogenous IL-33 to further confirm the initial data. Although IL-33 is not detectable in HCT-116 colon cancer cells ( 23 ), numerous other types of cells, including activated immune cells, fibroblasts and endothelial cells have been reported to produce IL-33 ( 24 ). Thus, it is possible that IL-33 produced by these cells may have an effect on the pathogenesis of colon cancer in a biological setting ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…HERVs are known to be de-silenced, and hence, transcriptionally activated in cancer. Accordingly, HERV transcriptional activity has been found to be significantly upregulated in cancer cells than in controls [ 73 , 80 , 86 , 109 , 110 , 111 ].…”
Section: New Insights On Herv Contribution To Human Pathophysiologmentioning
confidence: 99%